Representation of the phoneme [ŋ] at onset in Bahasa Indonesia speech as L3 in foreign speakers: A language typology perspective - Kholiq, Abdul; Yulianto, Bambang; Suhartono, Suhartono; Susanto, Moh. Arif; Azizan, Yoga Rifqi; Rizal, Moh. Ahsan Shohifur (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2026)
This study investigates the representation of the phoneme [ŋ] in the onset position of Bahasa Indonesia (BI) and the factors influencing its changes among foreign speakers learning BI as a third language (L3). It employed a qualitative approach. Five BIPA students served as subjects. Their L1 and L2 typological proximity to BI was determined by language-family classification. Data were collected through elicitation and interviews, and analysis involved comparing the representation of the phoneme [ŋ] in subjects' speech with standard BI speech. Results show that the representation of the phoneme [ŋ] in the onset position by subjects whose L1 is typologically close to BI aligns with standard BI speech. This is attributed to their L1 having a similar phonological system to BI. Conversely, for foreign speakers whose L1 and L2 are typologically distant from BI, their phonological systems exhibit differences in speech compared to standard BI. In the speech of these subjects, the representation of [ŋ] in the onset position shows specific alterations. These include: 1) the epenthesis of [g] after [ŋ]; and 2) the shifting of [ŋ] from the onset to the coda of the preceding syllable, with the original onset position then being replaced by [g]. Two factors influence these changes: 1) the phonological systems of L1 and L2 lack [ŋ] in the onset position, though they permit it in medial and final positions; and 2) foreign speakers misinterpret the /ng/ form as a sequence of [n] and [g] ([n-g]), which leads to pronunciation errors.